2007
DOI: 10.1007/s11814-007-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical properties of gel polymer electrolyte based on poly(acrylonitrile)-poly(ethylene glycol diacrylate) blend

Abstract: Gel type electrolyte was formulated by blending of PEDGA and PAN. PEDGA is a UV curable polymer which forms a chemical crosslink by UV or heat. Gel type electrolyte is very stable in ionic conductivity and interfacial resistance for a long storage time. It has the advantage of manufacturing the battery in a continuous process because oligomer crosslinking occurs in few seconds without heating. Discharge capacity and cycle life were increased by using LiPF 6 /LiCF 3 SO 3 mixed lithium salt and adding inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This study demonstrated that the ionic conductivity was enhanced when using an optimum TiO 2 loading (2 wt%) in the GPE. Byung et al [ 79 ] synthesized a GPE by blending poly(acrylonitrile)-poly(ethylene glycol diacrylate) (PAN-PEGDA) with Li-salt and TiO 2 NPs. The high surface area of inorganic fillers can improve the interfacial resistance and ionic conductivity of Li metal owing to an increase in chemical stability and possible retention of organic solvents in the micropores; this assists in the regulation of possible side reactions associated with Li metal.…”
Section: Details Of the Inorganic Fillers Applied In Gpesmentioning
confidence: 99%
“…This study demonstrated that the ionic conductivity was enhanced when using an optimum TiO 2 loading (2 wt%) in the GPE. Byung et al [ 79 ] synthesized a GPE by blending poly(acrylonitrile)-poly(ethylene glycol diacrylate) (PAN-PEGDA) with Li-salt and TiO 2 NPs. The high surface area of inorganic fillers can improve the interfacial resistance and ionic conductivity of Li metal owing to an increase in chemical stability and possible retention of organic solvents in the micropores; this assists in the regulation of possible side reactions associated with Li metal.…”
Section: Details Of the Inorganic Fillers Applied In Gpesmentioning
confidence: 99%
“…Moreover, acrylic fiber dyes very well and has excellent colorfastness. AN copolymers were used as polymer electrolytes, i.e., in Li‐polymer batteries,2–8 to produce conductive composites as thin films,9–11 or used as a fiber form,12, 13 with addition of salts or self‐dopant polymers to improve the electronic interaction of structure and dielectric and conductance properties. Electrostatic interaction increases by incorporation of a small amount of a sulfonate (SO 3 − ) or a carboxylate (COO − ) group in such composites, resulting in better electrical conductivity and improved morphologic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The SiC/C composites showed good oxidation resistance up to 830 • C. The effective mixing ratio of PCS/phenolic resin to prepare improved mechanical property was 2/1. Literature such as Park et al (1996), Sun et al (1998), Jeon and Yoo (1998), Lim et al (1999), Hwang and Chun (1999), Lee et al (1999), Cho et al (2007), Pattamarat and Hunsom (2008), Kim et al (2008), Joo et al (2008), Jeong et al (2008), andCho et al (2008) reported development and applications of electrodes.…”
Section: Introductionmentioning
confidence: 99%